Effect of chicken blood and intestines silages, as partial substitutes for fishmeal, on the growth of tilapia fingerlings (Oreochromis niloticus, Linnaeus, 1758) - Díaz-Cachay, Catalina (2023)
The inclusion of biological silage from chicken intestines and blood in the feed for Nilotic tilapia Oreochromis niloticus, substituting 80% of the protein content of fishmeal, was evaluated. The silages were made with 70% waste, 15% energy source (14% molasses and 1% sugar) and 15% yogurt (lactic acid bacteria). The pH and acidity were determined for 180 days, and the chemical analysis was done using standard methods. The base diet was formulated with the minimum cost equation, and considering the nutritional requirements for tilapia, inclusion levels and cost of inputs. A control diet and two with silages were used. The fingerlings (n=270) with an initial weight of 5.17 ± 0.18 g were randomly distributed in nine aquariums (3 per diet). The fish were fed three times a day and evaluated monthly. A significant difference (p<0.05) was found in the final weight and biomass averages between the control and silage. Feed conversion factor (FCA) and protein efficiency ratio (PER) were similar between diets (p>0.05). The cost to produce 1 kg of tilapia was lower in the diet with intestine silage (USD 1.16), followed by blood silage (USD 1.20), meaning a reduction in feeding costs of 29.26 and 26.48%, respectively.